PENGARUH AKTIVITAS DI BANTARAN SUNGAI CISADANE TERHADAP BEBAN PENCEMAR NITRAT DAN FOSFAT - Eva Pay; Widyo Astono; Diana Irvindiaty Hendrawan (Universitas Trisakti, 2021)
Activities in the Cisadane watershed can be a potential source of pollution resulting in reduced conservation areas, and increased pollutant loads from domestic or industrial waste. The purpose of this study was to determine the water quality of the Cisadane River and the effect of community activities on nitrate and phosphate parameters. This research was conducted from March to June 2021. The scope of the study area is the middle to downstream Cisadane River with 6 sampling locations, starting from the Teuku Umar Bridge to Muara Tanjung Burung along 34 km. The parameters used in this study were temperature, turbidity, DHL, pH, DO, nitrate and phosphate. The method used for the identification of pollutants is carried out by field surveys, water quality analysis is compared with quality standards according to PP No. 22 of 2021. The results of water quality analysis for nitrate parameters range from 0.7 mg/L–1.05 mg/L and phosphate parameters range from 0.7 mg/L–1.1 mg/L. Community activities around the river originating from settlements, agriculture, industry, and domestic activities from restaurants and stalls affect the quality of river water.